Study of cattle fattening system in selected region of Bangladesh - Kamal, MT; Hashem, MA; Mamun, M Al; Hossain, MM; Razzaque, MA (SAARC Journal of Agriculture, 2019)
The current study was undertaken to assess the present status of cattle mixed feeds, feed ingredients and use of growth promoters in livestock production of Bangladesh. The survey was carried out through a structured questionnaire among 80 farmers during April to June, 2017. The study revealed that agriculture is the primary occupation for 63% of respondents, whereas 27.5% of respondents are dependent over livestock. The dairy farmers are involved in both dairy and beef cattle fattening. Approximately 64% of the livestock farmers practiced fattening round the year and rest of the respondents followed fattening for period of 3 months; before Eid-ul-Adha. About 86% farmers reared uncastrated males instead of steer for fattening. It was observed that 59% of the farmers applying steroid as growth promoters in beef cattle fattening. The study indicated that middleman, feed/ medicine dealers were involved in promoting of steroids (dexavet, pednivet, oradexon, decason, paractin, gludex etc) usages in livestock. Owing to the lack of knowledge on steroids use in livestock over public health, the farmers are influenced by the vendors for quick profit. They sell their animals prior to withdrawal periods of drugs. Training and knowledge about the health hazards of steroids had inverse significant relationship with use of steroid as growth promoter (p<0.01). Improvement of education, training and financial status of the farmers significantly affected the use of steroids in beef fattening. Present problems could be addressed by intervention measures by the policy makers of the livestock sector. SAARC J. Agri., 17(1): 105-118 (2019)